Selective and differential interactions of BNN27, a novel C17-spiroepoxy steroid derivative, with TrkA receptors, regulating neuronal survival and differentiation. (December 2016) - Pediaditakis, Iosif; Efstathopoulos, Paschalis; Prousis, Kyriakos C.; Zervou, Maria; Arévalo, Juan Carlos; Alexaki, Vasileia I.; Nikoletopoulou, Vassiliki; Karagianni, Efthymia; Potamitis, Constantinos; Tavernarakis, Nektarios; Chavakis, Triantafyllos; Margioris, Andrew N.; et al.
Abstract: Nerve growth factor (NGF) holds a pivotal role in brain development and maintenance, been also involved in the pathophysiology of neurodegenerative diseases. Here, we provide evidence that a novel C17-spiroepoxy steroid derivative, BNN27, specifically interacts with and activates the TrkA receptor of NGF, inducing phosphorylation of TrkA tyrosine residues and down-stream neuronal survival-related kinase signaling. Additionally, BNN27 potentiates the efficacy of low levels of NGF, by facilitating its binding to the TrkA receptors and differentially inducing fast return of internalized TrkA receptors into neuronal cell membranes. Furthermore, BNN27 synergizes with NGF in promoting axonal outgrowth, effectively rescues from apoptosis NGF-dependent and TrkA positive sympathetic and sensory neurons, in vitro, ex vivo and in vivo in NGF null mice. Interestingly, BNN27 does not possess the hyperalgesic properties of NGF. BNN27 represents a lead molecule for the development of neuroprotective TrkA receptor agonists, with potential therapeutic applications in neurodegenerative diseases and in brain trauma. Graphical abstract: Highlights: Blood brain barrier-permeable C17-spiroepoxy steroid derivative, BNN27, specifically binds to and activates NGF receptor, TrkA. BNN27 differentially regulates TrkA endocytosis compared to NGF, inducing fast return of TrkA into cell membrane, potentiating the neuroprotective and neuritogenic effects of NGF. BNN27 effectively protects NGF-dependent sympathetic and sensory neurons from apoptosis, however is deprived of the hyperalgesic properties described for NGF. BNN27 may represent a lead molecule for neuroprotective and neurogenic therapeutics of neurodegenerative diseases and brain trauma.